Strategy synthesis resolving strategy paradoxes to create competitive advantage : concise version - Wit, Bob De (South-Western/Cengage Learning, 2010)
Helps students and professionals around the world develop into critical and creative strategic thinkers. Guiding readers through a variety of perspectives, this title shows how, more than ever, effective strategy requires the ability to consider strategic issues in many different ways